2016
DOI: 10.21037/tau.2016.07.02
|View full text |Cite
|
Sign up to set email alerts
|

Emphysematous pyelonephritis: the impact of urolithiasis on disease severity

Abstract: BackgroundEmphysematous pyelonephritis is a severe infection of the kidney associated with formation of gas in the renal parenchyma and/or collecting system. The purpose of this study was to evaluate outcomes of patients with emphysematous pyelonephritis in a contemporary cohort and to evaluate the impact of urolithiasis on disease severity.MethodsA search of all imaging reports at University of California San Francisco (UCSF) for the term “emphysematous pyelonephritis” was undertaken from 2003–2014. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
0
9
0
2
Order By: Relevance
“…The current treatment strategies include medical management (MM) alone, MM plus percutaneous catheter drainage (PCD), MM plus PCD plus double J stents, MM plus nephrectomy, and MM plus PCD plus emergency nephrectomy. These treatment strategies have shown lower mortality rates compared to the 1980s approach [ 2 , 7 , 17 , 18 ]. Over the last three decades, the treatment approach has favored kidney sparing strategies and the use of nephrectomy only as salvage therapy; however, multiple predictive factors for mortality have been identified, which can orient the medical team on which treatment strategy should be followed, expecting better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The current treatment strategies include medical management (MM) alone, MM plus percutaneous catheter drainage (PCD), MM plus PCD plus double J stents, MM plus nephrectomy, and MM plus PCD plus emergency nephrectomy. These treatment strategies have shown lower mortality rates compared to the 1980s approach [ 2 , 7 , 17 , 18 ]. Over the last three decades, the treatment approach has favored kidney sparing strategies and the use of nephrectomy only as salvage therapy; however, multiple predictive factors for mortality have been identified, which can orient the medical team on which treatment strategy should be followed, expecting better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli was still the most common pathogen; 4. older age, high bodymass index, impaired renal function, thrombocytopenia, sensory changes, and shock were associated with a poor prognosis; and 5. treatment mainly consisted of rapid hydration, maintenance of electrolyte balance, use of systemic antibiotics, strict control of blood glucose, effective urine drainage, and nephrectomy if necessary [1]. Sanford et al have shown that mild EPN was treatable by conservative management that included infectious agent-susceptible antibiotics [24]. However, patients with severe infections required percutaneous renal puncture drainage and/or double-J stenting [24].…”
Section: Discussionmentioning
confidence: 99%
“…Sanford et al have shown that mild EPN was treatable by conservative management that included infectious agent-susceptible antibiotics [24]. However, patients with severe infections required percutaneous renal puncture drainage and/or double-J stenting [24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that through pelvic nerve ES, certain muscles controlling bladder function can be activated, thus enabling researchers to control bladder function. [ 282,283 ] Currently, the main approach to treating bladder dysfunction is utilizing catheters. However, this approach has many shortcomings including the obvious downside that the individual must undergo frequent catheter changes.…”
Section: Neural Engineeringmentioning
confidence: 99%